Designing Stimulus as Cognitive Task Stimulus for Measurement of Cognitive Bias in Online Gamers - Diantina, Fanni Putri; Nawangsih, Endah; Permana, Rizka Hadian; Khasanah, Andhita Nurul; Hanifa, Fathiyya Amalia; Putri, Gitta Indriani Lestari; Shafana, Yasya Citra (Universitas Islam Bandung, 2025)
Problematic online gamers are shown to be biased towards information about gaming, focusing on it more than other subjects. Measuring cognitive processes requires tasks with specific stimuli, essential for studying decision-making. This research aims to create a gambling-related stimulus for a mental task. The research used a combination of methods. Qualitative data were gathered through interviews and focus group discussions, while quantitative data were collected through questionnaires. A total of 88 research participants were obtained by purposive sampling with inclusion criteria: aged 18–30, played games 4–10 hours daily for at least 12 months. Forty gamers participated in semi-structured interviews using an interview guide based on the Interaction of Person-Affect-Cognition-Execution (I-PACE) theoretical framework. Forty-eight gamers also took part in focus group discussions (FGDs). This research was conducted in Bandung from November 2023 to October 2024. The data were analyzed using NVivo-14 software and descriptive statistics. As a result, various stimuli were obtained, including 597-word stimuli, 87 image stimuli, and 97 audio stimuli. It was hypothesized that these stimuli would evoke a strong association with online games, prompting gamers to devote greater attention when encountering them, whether in visual, textual, or audio formats.